Influence of a Z+(1540) resonance on K+N scattering - Haidenbauer, J.; Krein, G. [UNESP] (Amer Physical Soc, 2003)
The impact of a (I=0, JP=1/2+)Z+(1540) resonance with a width of 5 MeV or more on the K+N(I=0) elastic cross section and on the P01 phase shift is examined within the KN meson-exchange model of the Jülich group. It is shown that the rather strong enhancement of the cross section caused by the presence of a Z + with the above properties is not compatible with the existing empirical information on KN scattering. Only a much narrower Z+ state could be reconciled with the existing data - or, alternatively, the Z + state must lie at an energy much closer to the KN threshold.